2017
DOI: 10.3390/cancers9030026
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Posttraumatic Stress and Posttraumatic Growth in Childhood Cancer Survivors

Abstract: This longitudinal study aims to analyze predictors of posttraumatic stress symptoms (PTSS) and posttraumatic growth (PTG) among gender, age, objective factors of the disease and its treatment, family environment factors and negative emotionality. The sample consisted of 97 childhood cancer survivors (50 girls and 47 boys) aged 11–25 years who were in remission 1.7 to seven years at T1 and four to 12.5 years at T2. Survivors completed a set of questionnaires including the Benefit Finding Scale for Children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 44 publications
3
36
0
Order By: Relevance
“…All these studies describe adult RB survivors as a fairly healthy and resilient group. Posttraumatic growth (PTG) may have played an important role among these RB survivors [14,15]. In our study, only unilateral RB survivors were included, we did not explore the difference between bilateral RB survivors and unilateral RB survivors.…”
Section: Discussionmentioning
confidence: 99%
“…All these studies describe adult RB survivors as a fairly healthy and resilient group. Posttraumatic growth (PTG) may have played an important role among these RB survivors [14,15]. In our study, only unilateral RB survivors were included, we did not explore the difference between bilateral RB survivors and unilateral RB survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the disease type and treatment factors, previous results have shown that chemotherapy and radiotherapy are related to PTG but not surgery . However, studies with survivors of different ethnicities have found opposite results . Additionally, some studies have reported that social support and positive coping styles are major positive factors influencing PTG .…”
Section: Introductionmentioning
confidence: 99%
“…According to Tedeschi's PTG theory, after survivors are initially diagnosed with cancer, they change their beliefs and behaviors and develop a life narrative and wisdom through recurrent rumination and coping. Researchers have reported factors that may influence PTG including sociodemographic variables, social support, and coping styles . With regard to sociodemographic variables, some studies have shown that higher levels of PTG in survivors are associated with older age, being female, being employed, higher educational level, higher household income, and religious beliefs .…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in pediatric psycho-oncology demonstrates that post-traumatic growth, marked by adaptive coping and resilience, can take place in the survivors 3436 as well as their parents/caregivers. 7,11 Consistent with this, our interview participants reported being able to cope using a variety of strategies, regardless of whether they were providing acupressure.…”
Section: Discussionmentioning
confidence: 99%